Thermal Conductivity of Carbon Pellets Prepared from Oil Palm Bunches - Deraman, Mohamad; Omar, Ramli (Universiti Putra Malaysia Press, 1997)
Factors such as its natural properties, low cost and availability in large quantities as a waste product may give oil palm empty fruit bunches (EFB) a great potential for use as a precursor for producing solid carbon electrodes and electrical components. One of the important properties of this product is its thermal conductivity. The thermal conductivity of carbon pellets prepared from fibres of oil palm empty fruit bunches was measured at the temperature of 150°C using the dynamic technique. The value obtained was 1.38 Wm'\ K', which is 2-5 times lower than the value predicted in this work, the value for carbon prepared from cellulose, the value for commercial carbon measured in this work and the value quoted by manufacturer for glassy carbon product. This difference is due to the microstructure of the EFB-earbon which is more porous than the other carbon products.